2017
DOI: 10.1172/jci88428
|View full text |Cite
|
Sign up to set email alerts
|

Matriptase-mediated cleavage of EpCAM destabilizes claudins and dysregulates intestinal epithelial homeostasis

Abstract: Congenital tufting enteropathy (CTE) is a severe autosomal recessive human diarrheal disorder with characteristic intestinal epithelial dysplasia. CTE can be caused by mutations in genes encoding EpCAM, a putative adhesion molecule, and HAI-2, a cell surface protease inhibitor. A similar phenotype occurs in mice whose intestinal epithelial cells (IECs) fail to express the tight junction-associated protein claudin-7. EpCAM stabilizes claudin-7 in IECs, and HAI-2 regulates the cell surface serine protease matrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(105 citation statements)
references
References 46 publications
(77 reference statements)
3
98
4
Order By: Relevance
“…Hepsin and TMPRSS3 are important for normal hearing1617. Defects in these TTSPs may lead to major diseases such as skin disorders1819, congenital or inflammatory diarrheal diseases202122, iron-deficiency anaemia232425, hypertension26272829, and hearing loss16.…”
mentioning
confidence: 99%
“…Hepsin and TMPRSS3 are important for normal hearing1617. Defects in these TTSPs may lead to major diseases such as skin disorders1819, congenital or inflammatory diarrheal diseases202122, iron-deficiency anaemia232425, hypertension26272829, and hearing loss16.…”
mentioning
confidence: 99%
“…Of note, patients with the syndromic‐form of congenital sodium diarrhea due to SPINT2 mutation show histopathological abnormalities consistent with those of congenital tufting enteropathy that is typically observed in mutation of the EPCAM gene encoding epithelial cell adhesion molecule (EpCAM) . Furthermore, in vitro study has indicated that dysfunction of HAI‐2/SPINT2 results in matriptase‐mediated EpCAM cleavage in Caco‐2 human intestinal epithelial cells . Thus, HAI‐2/SPINT2 may maintain the integrity of intestinal epithelium through regulation of the matriptase activity and EpCAM turnover.…”
Section: Hai‐1/spint1 and Hai‐2/spint2: Emerging Guardians Of Epithelmentioning
confidence: 95%
“…31,62 EPCAM is localized at the basolateral membrane of the epithelial cell and plays a role in the regulation of cell adhesion and proliferation via Claudin-7. 101 The syndromic form of CTE is characterized by choanal atresia, rarely intestinal atresia, and chronic diar-rhea. 88 Mutations of the SPINT2 gene that encodes a Kunitztype protease inhibitor have been described in syndromic CTE, as well as in cases of congenital sodium diarrhea, probably representing phenotypic diversity associated with the same mutation.…”
Section: Disorders Of Epithelial Trafficking and Polaritymentioning
confidence: 99%